2017
DOI: 10.1136/bjophthalmol-2017-310593
|View full text |Cite
|
Sign up to set email alerts
|

Bullous X linked retinoschisis: clinical features and prognosis

Abstract: Word Count: 1,375 2 SYNOPSIS:In a series of 9 patients with X-linked retinoschisis and bullous schisis cavities, associated ocular features included strabismus, vitreous haemorrhage, nystagmus, and persistent foetal vasculature. Retinal detachment was seen in 4 out of 18 eyes. 3 ABSTRACTBackground/Aims: A subset of patients with X-linked retinoschisis (XLRS) have bullous schisis cavities in the peripheral retina. This study describes the characteristics and prognosis of the bullous form of XLRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 9 publications
1
10
1
1
Order By: Relevance
“…Clinically, the disease is characterized in males by early-onset visual loss and bilateral foveal schisis due to splitting of the inner retinal layers; 33-60% of patients with XLRS also have peripheral retinoschisis [2][3][4]. Complications, such as retinal detachment, occur in 5-22% cases, and intraretinal haemorrhage within a schisis cavity or vitreous haemorrhage is present in approximately one third of patients [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, the disease is characterized in males by early-onset visual loss and bilateral foveal schisis due to splitting of the inner retinal layers; 33-60% of patients with XLRS also have peripheral retinoschisis [2][3][4]. Complications, such as retinal detachment, occur in 5-22% cases, and intraretinal haemorrhage within a schisis cavity or vitreous haemorrhage is present in approximately one third of patients [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, some authors recommend observation since spontaneous resolution has been reported. 5,11 Conversely, Hinds et al 8 found that three of nine patients with bullous schisis developed a tractional retinal detachment during the follow-up, and PPV in bullous schisis can reduce the size of the schisis and limit its progression. 17 In our series, patients who underwent PPV for vitreous hemorrhage showed a decrease in the height of their schisis and bullous schisis decreased in two eyes and completely resolved in one eye.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that this is a disease that slowly progresses with age (37,38). Furthermore, individuals harbouring the RS1 mutation display various clinical symptoms, including central retinal split, with or without a peripheral retinal split, macular hole, macular edema, retinal degeneration, retinal hemorrhage, retinal detachment and high myopia (39). Genetic modification and environmental factors that may be involved and the specific mechanisms require to be further explored.…”
Section: Discussionmentioning
confidence: 99%